Enhanced hydrogen evolution activity of CsPbBr3 nanocrystals achieved by dimensionality change. Issue 28 (20th March 2023) - Guo, Qing; Zhang, Jin-Dan; Chen, Ya-Jing; Zhang, Ke-Yuan; Guo, Li-Na; Shan, Qi-Chao; Lu, Jun-Lin; Duan, Xin-Hua; Wu, Li-Zhu
Abstract : In terms of facilitated photogenerated charge carrier dynamics and induced proton reduction potential, photocatalytic H2 evolution could be improved by dimensionality tuning from 3D nanocubes to 1D nanorods. Abstract : Dimensionality plays a vital role at the nanoscale in tuning the electronical and photophysical properties and surface features of perovskite nanocrystals. Here, 3D and 1D all-inorganic CsPbBr3 nanocrystals were chosen as model materials to systemically reveal the dimensionality-dependent effect in photocatalytic H2 evolution. In terms of facilitating photoinduced electron–hole pair separation and charge transfer, as well as inducing proton reduction potential with the presence of fewer Br vacancies, 1D CsPbBr3 nanorods gave about a 5-fold improvement for solar H2 evolution.